2005
DOI: 10.1002/jso.20265
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal sarcoma: 25 years of experience with aggressive surgical treatment at the Institute of Oncology, Ljubljana

Abstract: Complete surgical resection without microscopic residuum and contamination is likely to offer the best chances for long-term survival. Until there are no other treatment modalities, aggressive surgery for recurrent sarcoma is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 26 publications
5
50
0
5
Order By: Relevance
“…Patients with RSTS should receive treatment preferentially at high-volume centers 29,30 (see Table 1). In general, there are 2 ''surgery schools'': School 1 defends aggressive surgery, including reoperation and debulking in unresectable RSTS 2,23,34,35 ; whereas School 2 does not take this aggressive approach. 24,36,37 Subgroup analysis from the study by Gronchi et al demonstrated a benefit from aggressive surgery only for patients who received additional RT.…”
Section: Surgery Alonementioning
confidence: 99%
“…Patients with RSTS should receive treatment preferentially at high-volume centers 29,30 (see Table 1). In general, there are 2 ''surgery schools'': School 1 defends aggressive surgery, including reoperation and debulking in unresectable RSTS 2,23,34,35 ; whereas School 2 does not take this aggressive approach. 24,36,37 Subgroup analysis from the study by Gronchi et al demonstrated a benefit from aggressive surgery only for patients who received additional RT.…”
Section: Surgery Alonementioning
confidence: 99%
“…Leiomyosarcomas are soft tissue sarcomas and account for 1% of all solid malignancies in adults and approximately 15% of all soft tissue sarcomas [15,16]. According to a review of 36 cases with leiomyosarcomas, patients presenting with such tumors are aged 60 years, ranging from 12 to 94 years, at initial treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pathogenesis of leiomyosarcoma, a critical role for the AKT-mTOR pathway in smooth muscle transformation and leiomyosarcoma genesis has been newly proposed [42]. However, at present, the 5-year survival rate of the patients after complete tumor resection ranges from 40 to 70% [16]. High local recurrence rate and metastases tend to influence the survival although the size and histological type of the tumor do not affect it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Операции по поводу неорганных забрюшинных опухолей характеризуются сложностями, связанными с топографо-анатомическими особенностями за-брюшинного пространства, мультицентричностью зачатков опухоли, их агрессивным инвазивным ростом [23]. В настоящее время имеет место тен-денция к увеличению объема хирургических вме-шательств за счет расширенных комбинированных операций, частота которых составляет 37-75 %.…”
Section: варианты лечения злокачественных опухолей забрюшинного простunclassified